The relationship between pedestrian crash rates and injuries sustained and the location, time of day, traffic volume and the hypothetical travel speed at the time of the crash on the Gauteng Freeways - Snijder, Janneke (Stellenbosch : Stellenbosch University, 2019)
Thesis (MEng)--Stellenbosch University, 2019.